The Contribution of Chemoattractant GPCRs, Formylpeptide Receptors, to Inflammation and Cancer - Liang, Weiwei; Chen, Keqiang; Gong, Wanghua; Yoshimura, Teizo; Le, Yingying; Wang, Ying; Wang, Ji Ming (Frontiers in Endocrinology, 2020)
A hallmark of inflammatory responses is leukocyte mobilization, which is mediated by bacterial and host tissue-derived chemotactic factors that activate Gi-protein-coupled seven-transmembrane receptors (GPCRs) expressed on host cell surface. Formylpeptide receptors (FPRs, Fprs in mice) are members of the chemoattractant GPCR family, shown to be critical in myeloid cell trafficking during infection, inflammation, immune responses and cancer progression. Accumulating evidence demonstrates that both human FPRs and murine Fprs are involved in a number of patho-physiological processes because of their expression on a wide variety of cell types in addition to myeloid cells. The unique capacity of FPRs (Fprs) to interact with numerous structurally unrelated chemotactic ligands enables these receptors to participate in orchestrated disease initiation, progression and resolution. One murine Fpr member, Fpr2, and its endogenous agonist peptide, Cathelicidin-related antimicrobial peptide (CRAMP), have been demonstrated as key mediators of colon mucosal homeostasis and protection from inflammation and associated tumorigenesis. Recent availability of genetically engineered mouse models greatly expanded the understanding of the role of FPRs (Fprs) in pathophysiology that places these molecules in the list of potential targets for therapeutic intervention of diseases.